Continuity of care in lumbar disc herniation: a systematic review and meta-analysis providing a deeper look into postoperative efficacy - Ying Lin; Ying Lin; Qiaoling Chen; Qiaoling Chen; RouMei Wang; Bing Zhang; Bing Zhang; Rui Huang; Yiguang Bai; Yiguang Bai (Frontiers in Medicine, 2025)
BackgroundLumbar disk herniation is a prevalent spinal disorder. Continuity of care ensures seamless, coordinated, and high-quality management across healthcare transitions to optimize outcomes and reduce readmission risk. Insufficient structured postoperative care programs after diskharge may hinder recovery, lower quality of life, and increase complication risks.ObjectivesThis study aims to explore the significance of continuity of care in enhancing the recovery outcomes of patients with lumbar disk herniation post-surgery through a meta-analysis.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted an extensive search across several databases, including MEDLINE (PubMed), EMBASE, Web of Science, Google Scholar, CINAHL, EBSCO, Cochrane Library and Scopus, without restrictions on language or publication date. A meta-analysis was performed using both fixed-effects and random-effects models based on heterogeneity assessment. We analyzed the data using R software version 4.2.2 and Stata software version 15.1. The risk of bias was assessed using the Cochrane Risk of Bias Tool, the Newcastle-Ottawa Scale (NOS), funnel plots, sensitivity analysis, Egger’s test, and Begg’s test.ResultsThis study included a total of 15 studies, involving 1,804 participants. The meta-analysis results showed that the experimental group had significantly lower Visual Analog Scale (VAS), Oswestry Disability Index (ODI), and Self-Rating Anxiety Scale (SAS) scores 3 months post-operation compared to the conventional control group [SMD = −0.66, 95% CI (−0.91, −0.41), SMD = −0.91, 95%CI (−1.24, −0.58), SMD = −0.61, 95% CI (−0.91, −0.31), p < 0.01]. Additionally, the Japanese Orthopedic Association (JOA) score of the experimental group was significantly higher than that of the conventional control group at 3 months post-operation [SMD = 1.70, 95%CI (1.01, 2.39), p < 0.01].ConclusionOur meta-analysis indicates that continued care interventions significantly alleviate postoperative pain, enhance lumbar function, reduce anxiety, and improve overall functional recovery in LDH patients. High-quality continued care interventions are critical strategies for enhancing postoperative recovery outcomes. Nonetheless, as the included primary studies predominantly originate from China, further validation of these findings in diverse regions and populations is warranted in future research.Systematic review registrationPROSPERO https://www.crd.york.ac.uk/prospero/, identifier CRD42024604420.